Thermoelectric sheet, preparation method thereof and box girder bridge capable of generating power through temperature difference energy
By integrating thermoelectric sheets in steel plate-concrete bridge deck, the temperature difference is converted into electrical energy by combining bismuth telluride powder with high thermal conductivity polymer, the bridge durability and energy efficiency problems are solved, and the temperature difference power generation and intelligent monitoring functions are realized , reduce maintenance costs.
Patent Information
- Application Number
- CN202411417008.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-10
AI Technical Summary
During use, existing steel plate-concrete bridge deck box girder bridges are prone to affect their durability due to problems such as cracking of concrete and corrosion of steel bars, and cannot achieve temperature difference power generation, resulting in poor durability and energy efficiency of the bridge.
Thermoelectric sheet is adopted, including copper-clad ceramic upper substrate, copper-clad ceramic lower substrate, geopolymer bismuth telluride P-type thermoelectric particle column and geopolymer bismuth telluride N-type thermoelectric particle column. By combining bismuth telluride powder with environmental protection The thermally conductive geopolymer combines, using the Seebeck effect and the Peltier effect, converts the temperature difference into electrical energy, and is integrated into the steel plate-concrete bridge deck.
It realizes temperature differential energy generation, extends the service life of the bridge, provides renewable energy, reduces energy waste, monitors bridge temperature and stress changes in real time, reduces maintenance costs, and prevents snow and icing in winter.
Smart Images

Figure CN119300692A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a box girder bridge, in particular to a thermoelectric sheet and a preparation method thereof, and a box girder bridge capable of generating electricity by temperature difference. Background Art
[0002] The steel-concrete deck box girder bridge combines the advantages of steel and concrete, providing multiple benefits. First, this composite structure makes full use of the high strength and ductility of steel and the good compressive properties of concrete, significantly improving the bridge's load-bearing capacity and crack resistance, effectively preventing the formation of cracks and extending the service life of the bridge. At the same time, the combination of steel and concrete makes the bridge structure lighter, which is conducive to lightweight design and reduces the force requirements on piers and foundations. In addition, the steel-concrete bridge deck can be prefabricated in the factory, improving construction efficiency, reducing on-site construction time and costs, and reducing maintenance requirements and life cycle costs.
[0003] The existing steel plate-concrete deck box girder bridge is easily affected by problems such as concrete cracking and steel corrosion during use, and it is impossible to achieve temperature difference power generation. Summary of the invention
[0004] Purpose of the invention: In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide a thermoelectric sheet that can generate electricity and supply energy. Another purpose of the present invention is to provide a convenient and controllable method for preparing a thermoelectric sheet. Another purpose of the present invention is to provide a box girder bridge that can generate electricity by temperature difference and has good durability, energy saving and environmental protection.
[0005] Technical solution: A thermoelectric sheet described in the present invention includes a copper-clad ceramic upper substrate, a copper-clad ceramic lower substrate, a geopolymer bismuth telluride P-type thermoelectric particle column, a geopolymer bismuth telluride N-type thermoelectric particle column and a wire. The geopolymer bismuth telluride P-type thermoelectric particle column and the geopolymer bismuth telluride N-type thermoelectric particle column are interconnected and arranged in an array between the copper-clad ceramic upper substrate and the copper-clad ceramic lower substrate, and the wire is connected to the geopolymer bismuth telluride N-type thermoelectric particle column at both ends.
[0006] Furthermore, the geopolymer bismuth telluride P-type thermoelectric particle column and the geopolymer bismuth telluride N-type thermoelectric particle column are L-type.
[0007] The method for preparing the thermoelectric sheet comprises the following steps:
[0008] Step 1: After mixing metakaolin, slag and silica fume to obtain a gel material, first mix it with river sand, add bismuth telluride powder, and then add an alkaline activator;
[0009] Step 2, curing the product obtained in step 1, demolding and polishing after completion, to obtain geopolymer bismuth telluride thermoelectric particles, including P-type thermoelectric particles and N-type thermoelectric particles;
[0010] Step 3, uniformly electroplating the geopolymer bismuth telluride thermoelectric particles with a nickel layer and a tin layer to metallize their surface;
[0011] Step 4: print lead-free solder on the copper-clad ceramic lower substrate, place a mold, evenly sprinkle surface metallized P-type thermoelectric particles or N-type thermoelectric particles, vibrate the mold to make it fall into a designated position, remove excess particles on the mold, and then fill the surface metallized N-type thermoelectric particles or P-type thermoelectric particles to obtain geopolymer bismuth telluride P-type thermoelectric particle columns and geopolymer bismuth telluride N-type thermoelectric particle columns;
[0012] Step 5: After the filling is completed, the mold is removed, and the copper-clad ceramic upper substrate is positioned through the groove to cover the geopolymer bismuth telluride thermoelectric particles;
[0013] Step 6: Use the prepared mask to evenly apply solder paste on the copper electrode, take out the mask, and fill and fix the particles according to the previous steps;
[0014] Step 7: heating the product obtained in step 6 to ensure that the upper ends of the P-type thermoelectric particles and the N-type thermoelectric particles reach the melting temperature of the solder paste, and then cooling after keeping the temperature.
[0015] Step eight, welding the wires to the N-type particle column and the P-type particle column at both ends to complete the preparation of the thermoelectric sheet.
[0016] Furthermore, in step 1, the mass ratio of metakaolin, slag and silica fume is 70-90:5-20:5-10. The mass volume ratio of gel material, river sand, bismuth telluride powder and alkaline activator is 4:1:1-2:1.5. The alkaline activator is a strong alkali solution and a water glass solution in a mass ratio of 3:6-8. The stirring rate is 300-500 r / min, and the stirring time is 3-5 min.
[0017] Furthermore, in step 2, the curing temperature is 10 to 30° C., and the curing time is 12 to 36 hours.
[0018] Furthermore, the specific surface area of the slag is 600 to 800 m 2 / kg, 45μm square hole sieve residue <1%, the total content of Al2O3 and SiO2 in the slag is ≥50wt%, the particle size of silica fume is 0.1-0.3μm, and the specific surface area is 15000-30000m 2 / kg.
[0019] A box girder bridge capable of generating electricity by temperature difference of the present invention comprises a box girder and a steel plate-concrete composite bridge deck, wherein the steel plate-concrete composite bridge deck comprises an orthotropic steel bridge deck, a PBL shear key, a through steel bar, a concrete layer and a thermoelectric sheet, wherein the orthotropic steel bridge deck is provided with an array-distributed PBL shear key, a thermoelectric sheet and a concrete layer, and the through steel bar passes through the PBL shear key; the thermoelectric sheet comprises a copper-clad ceramic upper substrate, a copper-clad ceramic lower substrate, a geopolymer bismuth telluride P-type thermoelectric particle column, a geopolymer bismuth telluride N-type thermoelectric particle column and a conductor, wherein the copper-clad ceramic upper substrate and the copper-clad ceramic lower substrate are provided with mutually connected and array-distributed geopolymer bismuth telluride P-type thermoelectric particle column and a geopolymer bismuth telluride N-type thermoelectric particle column, and the conductor is connected to the geopolymer bismuth telluride N-type thermoelectric particle column.
[0020] Further, the perforated plates of the PBL shear key have a spacing of 450-500 mm, a height of 500-550 mm, and a diameter of the steel bars passing through is 12-16 mm. Preferably, the perforated plates of the PBL shear key have a spacing of 450 mm, and a height of 530 mm.
[0021] Furthermore, the preparation method of the concrete layer is: first dry-mix the cement, aggregate and admixture according to the designed mix ratio so that the components are evenly distributed. Add water and admixtures to the dry mix and then stir. The mixing time should be determined according to the type and capacity of the mixer, generally 2-3 minutes, to ensure that the concrete is evenly mixed and has good workability. Use an inserted vibrator or a flat vibrator to vibrate the concrete. The vibrator is inserted into the lower layer of concrete, and the vibration should be uniform to avoid excessive or insufficient vibration. The vibration time at each location is generally 5-15 seconds, until the surface of the concrete presents a uniform slurry, the bubbles are discharged, and it no longer sinks significantly. After pouring, keep it moist and stand for about 48 hours. After hardening, remove the mold, and then carry out high-temperature steam curing at a constant temperature of 90°C for 48 hours.
[0022] Working principle: Combining thermoelectric technology with bridge structure, using the Seebeck effect and Peltier effect of materials, direct conversion of thermal energy into electrical energy can be achieved. This technology has the advantages of light weight, small size, simple structure, no pollution, no noise, no mechanical transmission parts and high reliability. By combining bismuth telluride powder with environmentally friendly and highly thermally conductive geopolymers, and integrating thermoelectric materials, the temperature difference can be converted into electrical energy to power bridge health monitoring equipment. This solution of integrating steel-concrete bridge deck and thermoelectric technology, combining steel plate-concrete bridge deck steel beam bridge with thermoelectric sheets, can give full play to the advantages of both, not only improving the structural performance and safety of the bridge, but also realizing the effective use of energy, reducing maintenance costs, and enhancing the sustainability and environmental friendliness of the bridge. It is an important direction for future bridge design and construction.
[0023] Working principle: When there is a temperature difference between the two ends of different thermoelectric materials, the characteristics of the thermoelectric materials will generate an electromotive force at both ends of the material to form an electric current and produce a phenomenon of thermoelectric effect, so it is called temperature difference power generation. All thermal effects caused by current and electrical effects caused by temperature difference are thermoelectric effects. It includes five basic thermoelectric effect principles, and through these five thermoelectric effect principles, the conversion between thermal energy and electrical energy is realized. They are Peltier effect, Seebeck effect, Thomson effect, Joule effect and Fourier effect.
[0024] Beneficial effects: Compared with the prior art, the present invention has the following significant features:
[0025] 1. Bridge decks incorporating thermoelectric panels can utilize the generated electricity for self-monitoring and maintenance, extending the life of the bridge;
[0026] 2. The thermoelectric sheet can convert the heat absorbed by the bridge deck into electrical energy, while ensuring the high-strength bending resistance of the front panel, providing renewable energy, and forming a temperature difference between the heat generated outside the bridge deck and the steel plate, and generating electricity through the thermoelectric sheet (7) to supply energy for the box girder bridge. This method not only reduces energy waste, but also can provide energy for the lighting, monitoring and other systems of the bridge, reducing dependence on external power sources;
[0027] 3. Thermoelectric technology can monitor the temperature and stress changes of bridges in real time, and give early warning of possible structural damage or material aging, thus reducing the frequency and cost of bridge maintenance. At the same time, the self-heating function of thermoelectric materials in bridge decks can prevent snow accumulation and ice formation in winter, reduce the use of artificial snow removal and snow melting agents, and further reduce maintenance costs.
[0028] 4. Embedding thermoelectric panels into bridge decks can achieve multifunctional integration. In addition to basic load-bearing and protection functions, they can also provide intelligent sensing, temperature regulation and other functions to improve the overall efficiency of the bridge. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a schematic diagram of the structure of the present invention;
[0030] Figure 2 It is a structural schematic diagram of a steel plate-concrete composite bridge deck 8 of the present invention;
[0031] Figure 3 It is a schematic diagram of the structure of the thermoelectric sheet 6 of the present invention. DETAILED DESCRIPTION
[0032] In the following examples, the slag is from Datang Nanjing Power Plant, and other experimental materials are commercially available. The specific surface area of the slag is 600-800m 2 / kg, 45μm square hole sieve residue <1%, the total content of Al2O3 and SiO2 in the slag ≥50wt%. The particle size of silica fume is 0.1-0.3μm, and the specific surface area of silica fume is 15000-30000m 2 / kg.
[0033] like Figure 1 The steel beam of the box girder bridge of the temperature difference energy generation is made of Q345C material, and the bottom steel beam is composed of the bottom plate, inclined bottom plate, middle diaphragm, side diaphragm, middle web plate, anchor box, side web plate, cantilever arm, flange plate, etc. The beam sections are connected by bolts and welding, the middle web plate and its stiffening and transverse wet joint embedded plates are connected by high-strength bolts, and the rest are connected by welding.
[0034] like Figure 2 The steel plate-concrete composite bridge deck 8 includes an orthotropic steel bridge deck 9, a PBL shear key 10, a through steel bar 11, a concrete layer 10 and a thermoelectric sheet 6. The orthotropic steel bridge deck 9 is formed by welding a steel top plate, a diaphragm and a longitudinal stiffening rib. The orthotropic steel bridge deck 9 is provided with an array of PBL shear keys 10, thermoelectric sheets 6 and a concrete layer 10, and the through steel bar 11 passes through the PBL shear key 10. The opening plate spacing of the PBL shear key 10 is 450 to 500 mm, and the height is 500 to 550 mm. The spacing is preferably 450 mm, and the height is preferably 530 mm. The diameter of the through steel bar 11 includes two diameters of 12 mm and 16 mm, and the model is HRB400.
[0035] The preparation method of the concrete layer 10 is as follows: cement, aggregate and admixture are first dry mixed according to the designed mix ratio to make each component evenly distributed. Water and admixtures are added to the dry mix and then stirred. The mixing time should be determined according to the type and capacity of the mixer, generally 2-3 minutes, to ensure that the concrete is evenly mixed and has good workability. The concrete is vibrated using an inserted vibrator or a flat vibrator. The vibrator is inserted into the lower layer of concrete and should be vibrated evenly to avoid excessive or insufficient vibration. The vibration time at each location is generally 5-15 seconds until the concrete surface presents a uniform slurry, bubbles are discharged, and no longer sinks significantly. After pouring, keep it moist and stop for about 48 hours, remove the mold after hardening, and then carry out high-temperature steam curing at a constant temperature of 90°C for 48 hours. The cement uses C50 concrete produced by Qingdao Zhuonengda Building Technology Co., Ltd., which has high fluidity, high strength, no shrinkage during the hardening process, and excellent resistance to chloride ion corrosion. Aggregates include coarse aggregates (such as crushed stone) and fine aggregates (such as sand). Aggregates should have good gradation, be clean and free of impurities. The maximum particle size of coarse aggregate is generally controlled within 20mm. Mineral admixtures (such as fly ash, silica fume, mineral powder, etc.) can be selected according to specific requirements to improve the performance of concrete. Water reducers or high-efficiency water reducers (such as polycarboxylate water reducers) are often used to improve the working performance and durability of concrete.
[0036] like Figure 3 The thermoelectric sheet 6 includes a copper-clad ceramic upper substrate 1, a copper-clad ceramic lower substrate 2, a geopolymer bismuth telluride P-type thermoelectric particle column 3, a geopolymer bismuth telluride N-type thermoelectric particle column 4 and a wire 5. The geopolymer bismuth telluride P-type thermoelectric particle column 3 and the geopolymer bismuth telluride N-type thermoelectric particle column 4 are connected to each other and arranged in an array between the copper-clad ceramic upper substrate 1 and the copper-clad ceramic lower substrate 2, and the wire is connected to the geopolymer bismuth telluride N-type thermoelectric particle column 4. The geopolymer bismuth telluride P-type thermoelectric particle column 3 and the geopolymer bismuth telluride N-type thermoelectric particle column 4 are L-shaped.
[0037] Example 1
[0038] A method for preparing a steel plate-concrete composite bridge deck 8 comprises the following steps:
[0039] S1: The river sand and the cementitious material are stirred at a rate of 400r / min for 3min to mix, then the polybismuth telluride powder is added, and finally the alkali activator is added. The weight ratio of the river sand and the cementitious material is 1:4, the content of metakaolin in the cementitious material is 70wt%, the content of slag is 20wt%, the content of silica fume is 10wt%, the weight ratio of the total weight of the river sand and the cementitious material to the bismuth telluride powder is 100:20, the volume ratio of the total weight of the river sand and the cementitious material to the alkali activator is 100:30, and the alkali activator is a compound of 8mol / L NaOH solution and water glass solution in a weight ratio of 3:7.
[0040] S2: The intermediate material obtained in step S1 is transferred into an electrode mold and cured at a temperature of 20° C. for 24 hours, and then demolded and polished to obtain geopolymer bismuth telluride thermoelectric particles, including P-type thermoelectric particles and N-type thermoelectric particles.
[0041] S3: The geopolymer bismuth telluride thermoelectric particles obtained in step S2 are uniformly electroplated with a 7 μm nickel layer, and then electroplated with a 7 μm tin layer to metallize the surface of the geopolymer bismuth telluride thermoelectric particles.
[0042] S4: Place the copper-clad ceramic lower substrate 2 printed with lead-free solder on a matching metal table, then place the designed mold on the substrate, first evenly sprinkle the surface metallized thermoelectric particles obtained in step S3 on the mold, and then vibrate the mold to make the particles gradually fall to the correct position. The mold is a double-layer mold, the upper mold is turned upside down to fill in P / N type particles respectively, and the lower mold is used to screen P / N type particles to ensure that the two types of particles are not filled in incorrectly and are accurately positioned on the copper electrode of the ceramic substrate.
[0043] S5: Remove the upper mold layer, remove excess particles, then remove the first and second mold layers, turn them over to the other side and put them back on the metal table, and repeat another step S3 to fill the surface metallized particles.
[0044] S6: After all particles are filled, the geopolymer bismuth telluride P-type thermoelectric particle column 3 and the geopolymer bismuth telluride N-type thermoelectric particle column 4 are obtained. The fixed mold is removed, and then the upper substrate is positioned through the metal stage groove and covered on the upper end of the geopolymer bismuth telluride thermoelectric particle.
[0045] S7: Use the prepared mask to evenly apply the solder paste on the copper electrode 13, then take out the mask, and then use the previous method of filling particles to fill and fix the particles.
[0046] S8: After the above process is completed, the entire device is placed on the heating table and fixed, and then the temperature is raised to 350°C to ensure that the temperature of the upper end of the particles reaches the melting temperature of the solder paste. After a period of insulation, the entire device together with the fixed mold is placed on a water heat dissipation platform for cooling.
[0047] S9: Weld the wire 5 to the N-type particle column 4 and the P-type particle column 3 at both ends to obtain the thermoelectric sheet 6.
[0048] S10: Install the steel plate, the geopolymer thermoelectric sheet 6, the PBL shear key 10, the through-steel bars 11 and the formwork for pouring concrete.
[0049] S11: Dry mix cement, aggregate and admixtures according to the designed mix ratio to ensure uniform distribution of the ingredients. Add water and admixtures to the dry mix and then stir. The mixing time should be determined according to the type and capacity of the mixer, generally 2-3 minutes, to ensure that the concrete is mixed evenly and has good workability.
[0050] S12: Use an inserted vibrator or a flat vibrator to vibrate the concrete. Insert the vibrator into the lower layer of concrete and vibrate evenly to avoid excessive or insufficient vibration. The vibration time at each location is generally 5-15 seconds, until the concrete surface presents a uniform slurry, the bubbles are discharged, and it no longer sinks significantly. After pouring, keep it moisturized and stand for about 48 hours. After hardening, remove the mold, and then carry out high-temperature steam curing at a constant temperature of 90℃ for 48 hours to obtain the steel plate-concrete bridge deck A1.
[0051] Example 2
[0052] A method for preparing a steel plate-concrete composite bridge deck 8 comprises the following steps:
[0053] S1: The river sand and the cementitious material are stirred at a rate of 400r / min for 3min to mix, then the bismuth telluride powder is added, and finally the alkali activator is added. The weight ratio of the river sand and the cementitious material is 1:4, the content of metakaolin in the cementitious material is 70wt%, the content of slag is 20wt%, the content of silica fume is 10wt%, the weight ratio of the total weight of the river sand and the cementitious material to the bismuth telluride powder is 100:30, the volume ratio of the total weight of the river sand and the cementitious material to the alkali activator is 100:30, and the alkali activator is obtained by compounding 8mol / L NaOH solution and water glass solution in a weight ratio of 3:7.
[0054] S2: The intermediate material obtained in step S1 is transferred into an electrode mold and cured at a temperature of 10° C. for 36 hours, and then demolded and polished to obtain geopolymer bismuth telluride thermoelectric particles, including P-type thermoelectric particles and N-type thermoelectric particles.
[0055] S3: The geopolymer bismuth telluride thermoelectric particles obtained in step S2 are uniformly electroplated with a 7 μm nickel layer, and then electroplated with a 7 μm tin layer to metallize the surface of the geopolymer bismuth telluride thermoelectric particles.
[0056] S4: Place the copper-clad ceramic lower substrate 2 printed with lead-free solder on a matching metal table, and then place the designed mold on the substrate. First, evenly sprinkle the surface metallized thermoelectric particles obtained in step S3 on the mold, and then vibrate the mold to make the particles gradually fall to the correct position.
[0057] S5: Remove the upper mold layer, remove excess particles, then remove the first and second mold layers, turn them over to the other side and put them back on the metal table, and repeat another step S3 to fill the surface metallized particles.
[0058] S6: After all particles are filled, the geopolymer bismuth telluride P-type thermoelectric particle column 3 and the geopolymer bismuth telluride N-type thermoelectric particle column 4 are obtained. The fixed mold is removed, and then the upper substrate is positioned through the metal stage groove and covered on the upper end of the geopolymer bismuth telluride thermoelectric particle.
[0059] S7: Use the prepared mask to evenly apply the solder paste on the copper electrode 13, then take out the mask, and then use the previous method of filling particles to fill and fix the particles.
[0060] S8: After the above process is completed, the entire device is placed on the heating table and fixed, and then the temperature is raised to 350°C to ensure that the temperature of the upper end of the particles reaches the melting temperature of the solder paste. After a period of insulation, the entire device together with the fixed mold is placed on a water heat dissipation platform for cooling.
[0061] S9: Weld the wire 5 to the N-type particle column 4 and the P-type particle column at both ends to obtain the geopolymer thermoelectric sheet 6.
[0062] S10: Install the steel plate, geopolymer thermoelectric sheet 6, PBL shear key 10, through-steel bar 11 and formwork.
[0063] S11: Dry mix cement, aggregate and admixtures according to the designed mix ratio to ensure uniform distribution of the ingredients. Add water and admixtures to the dry mix and then stir. The mixing time should be determined according to the type and capacity of the mixer, generally 2-3 minutes, to ensure that the concrete is mixed evenly and has good workability.
[0064] S12: Use an inserted vibrator or a flat vibrator to vibrate the concrete. Insert the vibrator into the lower layer of concrete and vibrate evenly to avoid excessive or insufficient vibration. The vibration time at each location is generally 5-15 seconds, until the concrete surface presents a uniform slurry, the bubbles are discharged, and it no longer sinks significantly. After pouring, keep it moisturized and stand for about 48 hours. After hardening, remove the mold, and then carry out high-temperature steam curing at a constant temperature of 90℃ for 48 hours to obtain the steel plate-concrete bridge deck A2.
[0065] Example 3
[0066] A method for preparing a steel plate-concrete composite bridge deck 8 comprises the following steps:
[0067] S1: The river sand and the cementitious material are stirred at a rate of 400r / min for 3min to mix, then the bismuth telluride powder is added, and finally the alkali activator is added. The weight ratio of the river sand and the cementitious material is 1:4, the content of metakaolin in the cementitious material is 70wt%, the content of slag is 20wt%, the content of silica fume is 10wt%, the weight ratio of the total weight of the river sand and the cementitious material to the bismuth telluride powder is 100:40, the volume ratio of the total weight of the river sand and the cementitious material to the alkali activator is 100:30, and the alkali activator is a compound obtained by mixing 8mol / L NaOH solution and water glass solution in a weight ratio of 3:7.
[0068] S2: The intermediate material obtained in step S1 is transferred into an electrode mold and cured at a temperature of 30° C. for 12 hours, and then demolded and polished to obtain geopolymer bismuth telluride thermoelectric particles, including P-type thermoelectric particles and N-type thermoelectric particles.
[0069] S3: uniformly electroplating an 8 μm nickel layer on the geopolymer bismuth telluride thermoelectric particles obtained in step S2, and then electroplating an 8 μm tin layer, so as to metallize the surface of the geopolymer bismuth telluride thermoelectric particles.
[0070] S4: Place the copper-clad ceramic lower substrate 2 printed with lead-free solder on a matching metal table, and then place the designed mold on the substrate. First, evenly sprinkle the surface metallized thermoelectric particles obtained in step S3 on the mold, and then vibrate the mold to make the particles gradually fall to the correct position.
[0071] S5: Remove the upper mold layer, remove excess particles, then remove the first and second mold layers, turn them over to the other side and put them back on the metal table, and repeat another step S3 to fill the surface metallized particles.
[0072] S6: After all particles are filled, the geopolymer bismuth telluride P-type thermoelectric particle column 3 and the geopolymer bismuth telluride N-type thermoelectric particle column 4 are obtained. The fixed mold is removed, and then the upper substrate is positioned through the metal stage groove and covered on the upper end of the geopolymer bismuth telluride thermoelectric particle.
[0073] S7: Use the prepared mask to evenly apply the solder paste on the copper electrode 13, then take out the mask, and then use the previous method of filling particles to fill and fix the particles.
[0074] S8: After the above process is completed, the entire device is placed on the heating table and fixed, and then the temperature is raised to 350°C to ensure that the temperature of the upper end of the particles reaches the melting temperature of the solder paste. After a period of insulation, the entire device together with the fixed mold is placed on a water heat dissipation platform for cooling.
[0075] S9: Weld the wire 5 to the N-type particle column 4 and the P-type particle column at both ends to obtain the geopolymer thermoelectric sheet 6.
[0076] S10: Install the steel plate, geopolymer thermoelectric sheet 6, PBL shear key 10, through-steel bar 11 and formwork.
[0077] S11: Dry mix cement, aggregate and admixtures according to the designed mix ratio to ensure uniform distribution of the ingredients. Add water and admixtures to the dry mix and then stir. The mixing time should be determined according to the type and capacity of the mixer, generally 2-3 minutes, to ensure that the concrete is mixed evenly and has good workability.
[0078] S12: Use an inserted vibrator or a flat vibrator to vibrate the concrete. Insert the vibrator into the lower layer of concrete and vibrate evenly to avoid excessive or insufficient vibration. The vibration time at each location is generally 5-15 seconds, until the concrete surface presents a uniform slurry, the bubbles are discharged, and it no longer sinks significantly. After pouring, keep it moisturized and stand for about 48 hours. After hardening, remove the mold, and then carry out high-temperature steam curing at a constant temperature of 90℃ for 48 hours to obtain the steel plate-concrete bridge deck A3.
[0079] Example 4
[0080] A method for preparing a steel plate-concrete composite bridge deck 8 comprises the following steps:
[0081] S1: The river sand and the cementitious material are stirred at a rate of 400r / min for 3min to mix, then the bismuth telluride powder is added, and finally the alkali activator is added. The weight ratio of the river sand and the cementitious material is 1:4, the content of metakaolin in the cementitious material is 80wt%, the content of slag is 20wt%, the content of silica fume is 10wt%, the weight ratio of the total weight of the river sand and the cementitious material to the bismuth telluride powder is 100:30, the volume ratio of the total weight of the river sand and the cementitious material to the alkali activator is 100:30, and the alkali activator is a compound obtained by mixing 8mol / L NaOH solution and water glass solution in a weight ratio of 3:7.
[0082] S2: The intermediate material obtained in step S1 is transferred into an electrode mold and cured at a temperature of 20° C. for 24 hours, and then demolded and polished to obtain geopolymer bismuth telluride thermoelectric particles, including P-type thermoelectric particles and N-type thermoelectric particles.
[0083] S3: The geopolymer bismuth telluride thermoelectric particles obtained in step S2 are uniformly electroplated with a 78 μm nickel layer, and then electroplated with a 7 μm tin layer to metallize the surface of the geopolymer bismuth telluride thermoelectric particles.
[0084] S4: Place the copper-clad ceramic lower substrate 2 printed with lead-free solder on a matching metal table, and then place the designed mold on the substrate. First, evenly sprinkle the surface metallized thermoelectric particles obtained in step S3 on the mold, and then vibrate the mold to make the particles gradually fall to the correct position.
[0085] S5: Remove the upper mold layer, remove excess particles, then remove the first and second mold layers, turn them over to the other side and put them back on the metal table, and repeat another step S3 to fill the surface metallized particles.
[0086] S6: After all particles are filled, the geopolymer bismuth telluride P-type thermoelectric particle column 3 and the geopolymer bismuth telluride N-type thermoelectric particle column 4 are obtained. The fixed mold is removed, and then the upper substrate is positioned through the metal stage groove and covered on the upper end of the geopolymer bismuth telluride thermoelectric particle.
[0087] S7: Use the prepared mask to evenly apply the solder paste on the copper electrode 13, then take out the mask, and then use the previous method of filling particles to fill and fix the particles.
[0088] S8: After the above process is completed, the entire device is placed on the heating table and fixed, and then the temperature is raised to 350°C to ensure that the temperature of the upper end of the particles reaches the melting temperature of the solder paste. After a period of insulation, the entire device together with the fixed mold is placed on a water heat dissipation platform for cooling.
[0089] S9: Weld the wire 5 to the N-type particle column 4 and the P-type particle column at both ends to obtain the geopolymer thermoelectric sheet 6.
[0090] S10: Install the steel plate, geopolymer thermoelectric sheet 6, PBL shear key 10, through-steel bar 11 and formwork.
[0091] S11: Dry mix cement, aggregate and admixtures according to the designed mix ratio to ensure uniform distribution of the ingredients. Add water and admixtures to the dry mix and then stir. The mixing time should be determined according to the type and capacity of the mixer, generally 2-3 minutes, to ensure that the concrete is mixed evenly and has good workability.
[0092] S12: Use an inserted vibrator or a flat vibrator to vibrate the concrete. Insert the vibrator into the lower layer of concrete and vibrate evenly to avoid excessive or insufficient vibration. The vibration time at each location is generally 5-15 seconds, until the concrete surface presents a uniform slurry, the bubbles are discharged, and it no longer sinks significantly. After pouring, keep it moisturized and stand for about 48 hours. After hardening, remove the mold, and then carry out high-temperature steam curing at a constant temperature of 90℃ for 48 hours to obtain the steel plate-concrete bridge deck A4.
[0093] Example 5
[0094] A method for preparing a steel plate-concrete composite bridge deck 8 comprises the following steps:
[0095] S1: The river sand and the cementitious material are stirred at a rate of 400r / min for 3min to mix, then the bismuth telluride powder is added, and finally the alkali activator is added. The weight ratio of the river sand and the cementitious material is 1:4, the content of metakaolin in the cementitious material is 90wt%, the content of slag is 5wt%, the content of silica fume is 5wt%, the weight ratio of the total weight of the river sand and the cementitious material to the bismuth telluride powder is 100:30, the volume ratio of the total weight of the river sand and the cementitious material to the alkali activator is 100:30, and the alkali activator is a compound obtained by mixing 8mol / L NaOH solution and water glass solution in a weight ratio of 3:7.
[0096] S2: The intermediate material obtained in step S1 is transferred into an electrode mold and cured at a temperature of 30° C. for 24 hours, and then demolded and polished to obtain geopolymer bismuth telluride thermoelectric particles, including P-type thermoelectric particles and N-type thermoelectric particles.
[0097] S3: The geopolymer bismuth telluride thermoelectric particles obtained in step S2 are uniformly electroplated with a 7 μm nickel layer, and then electroplated with a 7 μm tin layer, so that the surfaces of the geopolymer bismuth telluride P-type thermoelectric particles (10) and the geopolymer bismuth telluride N-type thermoelectric particles (11) are metallized.
[0098] S4: Place the copper-clad ceramic lower substrate 2 printed with lead-free solder on a matching metal table, and then place the designed mold on the substrate. First, evenly sprinkle the surface metallized thermoelectric particles obtained in step S3 on the mold, and then vibrate the mold to make the particles gradually fall to the correct position.
[0099] S5: Remove the upper mold layer, remove excess particles, then remove the first and second mold layers, turn them over to the other side and put them back on the metal table, and repeat another step S3 to fill the surface metallized particles.
[0100] S6: After all particles are filled, the geopolymer bismuth telluride P-type thermoelectric particle column 3 and the geopolymer bismuth telluride N-type thermoelectric particle column 4 are obtained. The fixed mold is removed, and then the upper substrate is positioned through the metal stage groove to cover the upper end of the particle.
[0101] S7: Use the prepared mask to evenly apply the solder paste on the copper electrode 13, then take out the mask, and then use the previous method of filling particles to fill and fix the particles.
[0102] S8: After the above process is completed, the entire device is placed on the heating table and fixed, and then the temperature is raised to 350°C to ensure that the temperature of the upper end of the particles reaches the melting temperature of the solder paste. After a period of insulation, the entire device together with the fixed mold is placed on a water heat dissipation platform for cooling.
[0103] S9: Weld the wire 5 to the N-type particle column 4 and the P-type particle column at both ends to obtain the geopolymer thermoelectric sheet 6.
[0104] S10: Install the steel plate, geopolymer thermoelectric sheet 6, PBL shear key 10, through-steel bar 11 and formwork.
[0105] S11: Dry mix cement, aggregate and admixtures according to the designed mix ratio to ensure uniform distribution of the ingredients. Add water and admixtures to the dry mix and then stir. The mixing time should be determined according to the type and capacity of the mixer, generally 2-3 minutes, to ensure that the concrete is mixed evenly and has good workability.
[0106] S12: Use an inserted vibrator or a flat vibrator to vibrate the concrete. Insert the vibrator into the lower layer of concrete and vibrate evenly to avoid excessive or insufficient vibration. The vibration time at each location is generally 5-15 seconds, until the concrete surface presents a uniform slurry, the bubbles are discharged, and it no longer sinks significantly. After pouring, keep it moisturized and stand for about 48 hours. After hardening, remove the mold, and then carry out high-temperature steam curing at a constant temperature of 90℃ for 48 hours to obtain the steel plate-concrete bridge deck A5.
[0107] Test Case
[0108] The above embodiment was placed in a 37°C environment and tested under sunlight. The test results are shown in Table 1.
[0109] Table 1 Performance of steel plate-concrete composite bridge decks obtained in different embodiments
[0110]
[0111] It can be seen from the data in Table 1 that the steel plate-concrete bridge deck 8 used for temperature difference energy power generation of box girder bridges obtained by the present invention has stable performance and high temperature difference power generation efficiency and can be used in temperature difference energy power generation of box girder bridges.
Claims
1. A thermoelectric sheet, characterized in that: The invention comprises a copper-clad ceramic upper substrate (1), a copper-clad ceramic lower substrate (2), a geopolymer bismuth telluride P-type thermoelectric particle column (3), a geopolymer bismuth telluride N-type thermoelectric particle column (4) and a wire (5), wherein the geopolymer bismuth telluride P-type thermoelectric particle column (3) and the geopolymer bismuth telluride N-type thermoelectric particle column (4) are arranged between the copper-clad ceramic upper substrate (1) and the copper-clad ceramic lower substrate (2), and the wire is connected to the geopolymer bismuth telluride N-type thermoelectric particle column (4) at both ends.
2. A thermoelectric sheet according to claim 1, characterized in that: The geopolymer bismuth telluride P-type thermoelectric particle column (3) and the geopolymer bismuth telluride N-type thermoelectric particle column (4) are L-type.
3. The method for preparing a thermoelectric sheet according to claim 1, characterized in that: The following steps are involved: Step 1: After mixing metakaolin, slag and silica fume to obtain a gel material, first mix it with river sand, add bismuth telluride powder, and then add an alkaline activator; Step 2, curing the product obtained in step 1, demolding and polishing after completion, to obtain geopolymer bismuth telluride thermoelectric particles, including P-type thermoelectric particles and N-type thermoelectric particles; Step 3, uniformly electroplating the geopolymer bismuth telluride thermoelectric particles with a nickel layer and a tin layer to metallize their surface; Step 4: print lead-free solder on the copper-clad ceramic lower substrate (2), place a mold, evenly sprinkle surface metallized P-type thermoelectric particles or N-type thermoelectric particles, vibrate the mold to make it fall into a designated position, remove excess particles on the mold, and then fill another surface metallized N-type thermoelectric particle or P-type thermoelectric particle to obtain a geopolymer bismuth telluride P-type thermoelectric particle column (3) or a geopolymer bismuth telluride N-type thermoelectric particle column (4); Step 5: After the filling is completed, the mold is removed, and the copper-clad ceramic upper substrate (1) is positioned through the groove to cover the geopolymer bismuth telluride thermoelectric particles; Step 6: Use the prepared mask to evenly apply solder paste on the copper electrode (13), take out the mask, and fill and fix the particles according to the previous steps; Step 7: heating the product obtained in step 6 to ensure that the upper ends of the P-type thermoelectric particles and the N-type thermoelectric particles reach the melting temperature of the solder paste, and then cooling after keeping the temperature. Step eight, welding the wire (5) to the N-type particle column (4) and the P-type particle column (3) at both ends to complete the preparation of the thermoelectric sheet (6).
4. The method for preparing a thermoelectric sheet according to claim 3, characterized in that: In the step 1, the mass ratio of metakaolin, slag and silica fume is 70-90:5-20:5-10.
5. The method for preparing a thermoelectric sheet according to claim 3, characterized in that: In the step 1, the mass volume ratio of the gel material, river sand, bismuth telluride powder and alkaline activator is 4:1:1 to 2:1.
5.
6. The method for preparing a thermoelectric sheet according to claim 3, characterized in that: In the step 1, the alkaline activator is a strong alkali solution and a water glass solution in a mass ratio of 3:6-8.
7. The method for preparing a thermoelectric sheet according to claim 3, characterized in that: In the step 1, the stirring rate is 300-500 r / min, and the stirring time is 3-5 min.
8. The method for preparing a thermoelectric sheet according to claim 3, characterized in that: In the step 2, the curing temperature is 10 to 30° C., and the curing time is 12 to 36 hours.
9. A box girder bridge capable of generating electricity by using temperature difference, characterized in that: The invention comprises a box girder (7) and a steel plate-concrete composite bridge deck (8), wherein the steel plate-concrete composite bridge deck (8) comprises an orthotropic steel bridge deck (9), a PBL shear key (10), a through steel bar (11), a concrete layer (12) and a thermoelectric sheet (6), wherein the orthotropic steel bridge deck (9) is provided with an array-distributed PBL shear key (10), a thermoelectric sheet (6) and a concrete layer (12), wherein the through steel bar (11) passes through the PBL shear key (10); and the thermoelectric sheet ( 6) comprising a copper-clad ceramic upper substrate (1), a copper-clad ceramic lower substrate (2), a geopolymer bismuth telluride P-type thermoelectric particle column (3), a geopolymer bismuth telluride N-type thermoelectric particle column (4) and a wire (5), wherein the geopolymer bismuth telluride P-type thermoelectric particle column (3) and the geopolymer bismuth telluride N-type thermoelectric particle column (4) are arranged between the copper-clad ceramic upper substrate (1) and the copper-clad ceramic lower substrate (2), and the wire is connected to the geopolymer bismuth telluride N-type thermoelectric particle column (4).
10. The box girder bridge capable of generating electricity by using temperature difference according to claim 9, characterized in that: The perforated plates of the PBL shear key (10) have a spacing of 450 to 500 mm and a height of 500 to 550 mm, and the diameter of the through steel bar (11) is 12 to 16 mm.
Citation Information
Cited By
Multilayer thermoelectric power generation device used in refuse landfill
CN120768156A